Preliminary sub-acute toxicological assessment of methanol leaves extract of Culcasia angolensis (Araceae) in Wistar rats - Abraham, Idagu Godwin (2023)
The CAE contains cardiac glycosides, alkaloids, tannins, flavonoids, steroids, saponins, and terpenoids. The oral LD50 was above 5 g/kg. There was a remarkable decline in the weekly body weight at all the CAE doses. The CAE increased the lymphocytes, aspartate transaminase, and urea. However, the levels of alanine transaminase and alkaline phosphatase were elevated remarkably. The histological studies did not reveal any serious organs abnormalities.